2020
DOI: 10.1039/d0cp00167h
|View full text |Cite
|
Sign up to set email alerts
|

Potential molecular semiconductor devices: cyclo-Cn (n = 10 and 14) with higher stabilities and aromaticities than acknowledged cyclo-C18

Abstract: The successful isolation of cyclo-C18 in experiment means the ground-breaking epoch of carbon rings. Herein, we studied the thermodynamic stabilities of cyclo-Cn (4 ≤ n ≤ 34) with density functional theory. When n = 4N + 2 (N is integer), cyclo-Cn (10 ≤ n ≤ 34) were thermodynamically stable. Especially, cyclo-C10 and cyclo-C14 were thermodynamically, kinetically, dynamically, and optically preferred to cyclo-C18, and were the candidates of zero-dimension carbon rings. The carbon atoms were sp hybridization in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 74 publications
(70 reference statements)
1
45
0
Order By: Relevance
“…Cyclo [18]carbon (C 18 ), a closed-loop polyyne of 18 sp-hybridized carbon atoms joined together, is one of the hottest molecule recently. Due to its unique molecular geometry and electronic structure, C 18 has quickly attracted extensive attentions from chemists after being generated and observed in condensed phase in 2019 1 and soon received wide investigations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Our group has also made a series of theoretical studies on it, including aromaticity, optical properties, intermolecular interaction, vibrational spectra, and so on [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclo [18]carbon (C 18 ), a closed-loop polyyne of 18 sp-hybridized carbon atoms joined together, is one of the hottest molecule recently. Due to its unique molecular geometry and electronic structure, C 18 has quickly attracted extensive attentions from chemists after being generated and observed in condensed phase in 2019 1 and soon received wide investigations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Our group has also made a series of theoretical studies on it, including aromaticity, optical properties, intermolecular interaction, vibrational spectra, and so on [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cyclic carbon chains (for brevity, denoted as c-CC[n] (see Fig. 1b)), which are the monocyclic isomers of linear carbon chains, have also attracted considerable attention in recent years [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . Note that c-CC [n] (where the carbon atoms are also sp-hybridized) are hypothesized to be the building blocks of fullerenes in the initial stages of growth 21 .…”
mentioning
confidence: 99%
“…Among them, c-CC [18] has recently been synthesized 26 , and some of the electronic properties of c-CC [18] have been reported. There are also a few theoretical studies on the electronic properties and applications of c-CC [18] and other cyclic carbon chains 22,[27][28][29][30][31][32][33][34][35][36][37][38] . For example, c-CC [18] has been found to possess electron-acceptor properties, and can be dubbed as the smallest all-carbon electron acceptor 28 .…”
mentioning
confidence: 99%
“…A very recent study by Li et al 53 probed the structures and stabilities of carbon rings and demonstrated the geometries of carbon rings C n ( n = 10 34 ) to be circular. Therefore, in the continuum model, a carbon ring is modeled as a circular ring of radius b possessing uniform distribution of carbon atoms and a CNT is modeled as a cylinder of radius a with a surface of uniformly distributed carbon atoms.…”
Section: Theoretical Methodologymentioning
confidence: 99%